2016
DOI: 10.1063/1.4945447
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of the effect of fluorine atoms on the crystal structure and semiconducting properties of poly(arylene-ethynylene) derivatives

Abstract: The effect of fluorine substitution on the molecular structure, crystal packing, and n-type semiconducting properties of a set of poly(arylene-ethynylene) polymers based on alternating thiadiazole and phenyl units linked through ethynylene groups has been studied by means of Density Functional Theory. As a result, an enlargement in the interplanar distance between cofacial polymer chains, as well as a decrease of the electronic coupling and electron mobility is predicted. On the other hand, fluorination could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 74 publications
5
37
0
Order By: Relevance
“…Note that oligomers with different chain length (n = 3 − 15) were generated by replication of the minimal periodic motif, which was previously optimized at the same level of theory and in those cases the free valences were saturated with hydrogen atoms. 21,23,32,[67][68][69] We have observed that this procedure allows calculating electronic properties in long oligomeric chains with a great reduction of the computational cost, and without significantly affecting the optical band gap. 21 The values of the optical band gap for the ideal polymer chains were estimated through the equation proposed by Meier et al 70 Page 11 of 53…”
Section: Computational Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…Note that oligomers with different chain length (n = 3 − 15) were generated by replication of the minimal periodic motif, which was previously optimized at the same level of theory and in those cases the free valences were saturated with hydrogen atoms. 21,23,32,[67][68][69] We have observed that this procedure allows calculating electronic properties in long oligomeric chains with a great reduction of the computational cost, and without significantly affecting the optical band gap. 21 The values of the optical band gap for the ideal polymer chains were estimated through the equation proposed by Meier et al 70 Page 11 of 53…”
Section: Computational Detailsmentioning
confidence: 99%
“…Both charge transfer rate constants estimated for polymer I are higher 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 30 than the rate constant reported for polymers containing Th and TT units (VII and VIII). 23,33 Hence, the use of TTh instead of Th and TT could improve the semiconducting properties of these PAEs. The highest rate constants for both electron and hole transport and, therefore, the most efficient charge transport were predicted for polymer IV.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
See 3 more Smart Citations